PEMANFAATAN KONTEN VISUAL NETIZEN DALAM MEMPROMOSIKAN HIDDEN GEM PARIWISATA BALI PADA AKUN INSTAGRAM @OTW_MELALI - Jeremy Purba, Ido Hady; Indrawati, Yayu; Kristianto, Yohanes (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 1 (2024): Jurnal IPTA (July 2024)DO - 10.24843/IPTA.2024.v12.i01.p08, 2024)
The @otw_melali Instagram account is an account that plays a role in informing and promoting hidden gems of Bali tourism by utilizing visual content owned by netizens to be reposted. In social media management, there are four important variables, namely context, communication, collaboration, connection that must be optimized so that the account's objectives can be achieved. In addition, there is a motive for community participation behind community participation in creating content that is reposted on @otw_melali. This study was conducted to analyze what factors influence netizen participation in creating visual content that is reposted on the @otw_melali Instagram account and also to evaluate whether the strategy used is an optimal strategy in utilizing netizen participation to promote Bali's hidden gems.The sampling technique used purposive sampling technique by distributing 100 questionnaires to netizens whose visual content had been reposted on Instagram @otw_melali. The data analysis technique used is descriptive qualitative and descriptive quantitative techniques with data collection techniques, namely archival data, elicitation data, and field note data. Based on the results of calculations using spss software, the results show that the factors that influence netizen participation in creating visual content are religious motive factors, context factors, connection factors, collaboration factors, economic motive factors, and communication factors. Moreover, it was found that all indicators of the 4C theory, namely context, communication, collaboration, connection which became the basic foundation of the Instagram @otw_melali strategy in utilizing netizen participation to promote Bali's hidden gems have been optimally implemented in the management of the @otw_melali Instagram account.